Exergy, techno-economic and exergoeconomic analyses for improving energy efficiency of a typical sugar mill and designing integrated biorefineries - Dogbe, Eunice Sefakor (Stellenbosch : Stellenbosch University., 2020)
Thesis (PhD)--Stellenbosch University, 2020.